Model for end-stage liver disease (MELD) score as a predictor and monitor of mortality in patients with Vibrio vulnificus necrotizing skin and soft tissue infections. - Kuo-Chin Huang; Yao-Hung Tsai; Kuo-Chung Huang; Mel S Lee (Public Library of Science (PLoS), 2015)
BACKGROUND:Vibrio vulnificus necrotizing skin and soft tissue infections (VNSSTIs) usually predispose patients with or without preexisting liver disease to septic shock, and then evolve to multiple organ dysfunction syndrome (MODS), thus resulting in high mortality in humans. However, clinicians do not have a valid prediction model to provide a reliable estimate of case-fatality rate when caring for these acutely and/or critically ill patients. METHODS/PRINCIPAL FINDINGS:We retrospectively analyzed 39 consecutive patients with VNSSTIs (mean age: 65.7 ± 11.3 years) at our institution between 2007 and 2010. All patients were treated with the same protocol. Demographic and clinical characteristics, disease severity on admission, treatment details, and outcomes were collected for each patient and extracted for analyses. We studied the predictive value of the model for end-stage liver disease (MELD), modified MELD including sodium (MELD-Na), and laboratory risk indicator for necrotizing fasciitis (LRINEC) scores for case-fatality. Logistic regression and receiver operating characteristic (ROC) curve analyses were performed. The mean MELD, MELD-Na and LRINEC scores on admission were 15.1 ± 1.1, 17.7 ± 1.1, and 3.4 ± 0.4 points, respectively. After admission, these patients had temporary or progressive deterioration of nearly all their scores and lab values. The area under the ROC curve for the MELD and ΔMELD scoring models were 0.929 (p = 0.002) and 0.897 (p = 0.005), respectively. An optimal MELD/ΔMELD cutoff value ≥ 20/2 had a good sensitivity and specificity (all > 80%), with a 64/13-fold increased odds for case-fatality. Additionally, the development of severe forms of anemia (p = 0.014) and hypoalbuminemia (p = 0.019) were associated with an increased case-fatality rate. DISCUSSION:The MELD/ΔMELD scoring model is an effective risk stratification indicator at the time of admission and also an excellent condition monitor during hospitalization for medical care of acutely and/or critically ill patients with VNSSTIs.